Pluralismo religioso, Storia delle religioni e progetti europei: Presupposti teorici e attuazioni pratiche (2002-2017) - Bernardo, Angela di (Studi e materiali di storia delle religioni, 2017)
In a time of global changes, migrations and increasing difficulties related to the management, but primarily to the understanding of the emerging cultural and religious complexity in contemporary societies, "religious pluralism" represents a significant topic that has received and continues to receive, from various points of view and for several reasons, a high degree of attention. Within the framework outlined by the project funded by the European Commission in the period 2002-2017, this work analyzes the peculiarities of the relationships existing between religious pluralism, History of Religions and European projects, in order to verify what have been the theories and practices that have characterized the success and achievement of the winning proposals, what has been-if any-the contribution offered by the historicalreligious studies, within the projects related to the area of study on "religious pluralism" and what could be the contribution of the disciplines indicated above to the future prospects imagined by the current development strategies and policies, while having, at the same time, the opportunity to identify the typical features of the connotations assumed by the concept of "religious pluralism" and by the related ideas, in the fields covered by this research. (English)